First description of the tadpole of Kurixalus baliogaster (Inger, Orlov, and Darevsky, 1999) (Anura: Rhacophoridae) from Vietnam, with comments on reproductive biology - Kropachev, Ivan I.; Vassilieva, Anna B.; Orlov, Nikolai L.; Rybaltovsky, Evgeny M.; Nguyen, Tao Thien (Zootaxa, 2021)
To date, 20 species of Kurixalus Ye, Fei, and Dubois have been described, and all of these species are distributed throughout South and Southeast Asia, from eastern India, throughout Myanmar and the mountainous regions of southern China, to Indochina, western and northern peninsular Thailand, Malaysia, Sumatra, Borneo, and the Philippines (Frost 2021). Descriptions of the tadpoles of only 6 species have been published: K. berylliniris and K. wangi Wu, Huang, Tsai, Li, Jhang, & Wu (Wu et al. 2016); K. eiffingeri (Boettger) (Kuramoto & Wang 1987); K. idiootocus (Kuramoto & Wang) (Kuramoto & Wang 1987); K. cf. verrucosus (Boulenger) (Ziegler & Vences 2002), and Kurixalus yangi Yu, Hui, Rao, & Yang (Humtsoe et al. 2020). A description of the tadpoles of K. baliogaster (Inger, Orlov, & Darevsky) is also given in the species description (Inger et al. 1999), but described larvae are “assigned tentatively to this species” in the published text. Additional studies on the identification of the conspecificity of the described tadpoles with K. baliogaster have not been conducted. Based on the much larger size of the tadpole body (TL up to 40.3 mm), as well as the labial tooth row formula 6(2–6)/5(1) given by Inger et al. (1999), we concluded that these described tadpoles cannot be larval K. baliogaster and most likely belong to some other species of rhacophorid frogs.